Improvement of tribological performance of CrN coating via multilayering with VN - Qiu, Yuexiu (2013)
To improve the tribological performance of CrN coating, VN was introduced to form the CrN/VN multilayer structure via magnetron sputtering. The CrN/VN multilayer coatings with bilayer periods of 7, 13 and 27 nm were investigated on the mechanical and tribological properties. The coatings were deposited on SUS420 and Si wafers (100) via in-line magnetron sputtering system. X-ray diffractometer, scanning electron microscopy, transmission electron microscopy and electron probe micro-analyzer were used to characterize the microstructures and chemical contents. Ball-on-disc wear test was used for tribological studies. The wear debris was analyzed by X-ray photoelectron spectroscopy. A hardness of 25.2 GPa and coefficient of friction of 0.21 were achieved for multilayered coating in contrast to 16.7 GPa in hardness and 0.4 in coefficient of friction for CrN coating.